Pengaruh Bauran Pemasaran (4P) Terhadap Minat Menggunakan Produk Tabungan Emas Pada Pegadaian Syariah - Jauhara Zakiyah Iffah; Liza Fibrianti; Yuni Astuti (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2023)
This research is aimed to analyze the influence of marketing mix (4P: Product, Place, Price, and Promotion) in using gold saving Product for Faculty of Economic and Business Islam (FEBI) students Raden Mas Said State Islamic University Surakarta. This research is descriptive quantitative. Questionnaires were distributed to 120 students of FEBI Raden Mas Said State Islamic University Surakart a . The data were tested validity with Confirmatory Factor Analysis (CFA) and reliability with Alpha Cronbach formula to test the of the research instrument. The hypothesis were analyzed by multiple regression analysis using SPSS version 23. This study found that the independent variables in this study simultaneously influenced the interest variable in using Gold Savings Products at Pegadaian Sharia. This study found that the marketing mix (4P), namely place, price, product and promotion, partially only product variables that did not affect the interest in saving gold.